Enhancement of the thermal stability and mechanical properties of recycled low density polyethylene/wheat biocomposite films with targeted repairing technology and network skeleton construction. (October 2019) - Xiao, Dingtian; Qing, Shan; Yu, Zhifeng; Xiao, Huaqiang
In this paper, biocomposite films were prepared by using recycled low density polyethylene from marine plastic waste and wheat straw micropowders from common agricultural wastes in northern China. In order to determine the optimal ratio, eight experimental groups were set up for comparative testing. For further improving the performance of the biocomposite film, the three-dimensional network skeleton construction and targeted repairing technology of the material were designed. The specimens were characterized by a HD camera, a universal examination machine, a research grade inverted microscope, and a thermogravimetric analyzer. The results indicate that the agglomeration of powders reduces the tensile strength of the material, and the elongation at break depends on the properties of the polyolefin matrix itself. The reinforced biocomposite film has a 13.7 MPa tensile strength and a 243% elongation at break. It has slightly better mechanical properties than ordinary materials, which can be used as an economical, thermally stable, and environmentally friendly material to manufacture new packaging and courier bags.